Illusion of Social Mobility: Reading Status and Social Honor in George Saunders’ Tenth of December - Upadhyay , Toya Nath; Paudyal, Janak (Literary Studies, 2025)
This study critically examines the intersection of class, status and bureaucracy in George Saunders’ selected stories from his Tenth of December through the theoretical framework of critical class analysis outlined by Max Weber. In contrast to traditional Marxism’ emphasis on class struggle and economic exploitation, Weberian sociology outlines a more intricate perspective by delineating class as market position, status as social honor, and bureaucracy as institutional control. Saunders’ narratives expose the illusion of social mobility, demonstrating how economic precarity, status anxieties and bureaucratic constraints shape individual agency and reinforce social stratification. This paper investigates how status-driven consumption, hierarchical exclusion and impersonal institutions perpetuate class-based insecurities into the stories. By analyzing the stories employing Weberian lens, the paper finds that Saunders’ fiction serves as a socioeconomic critique of contemporary American society, wherein structural inequalities, symbolic markers of prestige, and bureaucratic rationalization function as mechanisms of disenfranchisement. This study contributes to broader discussions on class identity, cultural capital, and institutional power in literary discourse, highlighting the enduring tensions between economic determinism and social stratification in neoliberal economies.